Intangible Cultural Heritage in Ukraine from Community to State: A General Survey of the Current Situation - Demian, Valentyna (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
The article focuses on the processes that have taken place and are taking place after Ukraine ratified the UNESCO Convention for the Safeguarding of Intangible Cultural Heritage in 2008. My analysis focuses on the legal aspects and institutional development. In particular, I assess the activities of stakeholder organizations and the role of communities in safeguarding ICH. I highlight the role of ICH in emergency situations, in particular during the current Russian war in Ukraine. Progress and engagement with the Convention accelerated and diversified greatly in the last two years. The Ministry of Culture and Information Policy of Ukraine has become more open and flexible. Public, governmental organizations, NGOs, museums, libraries, oblast cultural centres, educational and research institutions, as well as practitioners have all contributed to tangible progress in building policy and institutional capacity.